Susceptibility of Rats of Different Ages to Inoculation with Swine Haemagglutinating Encephalomyelitis Virus (a Coronavirus) by Various Routes - Hirano, N. (J Comp Pathol, 2001)
Haemagglutinating encephalomyelitis virus, strain 67N, was used to inoculate 1-, 2-, 4- and 8-week-old rats by the intracerebral (i.c.), intranasal (i.n.), intraperitoneal (i.p.), subcutaneous (s.c.), intravenous (i.v.) and oral routes with graded doses. The routes of infection, in descending order of efficacy, were: i.ci.ns.ci.pi.v. and oral. Rats aged 1 and 2 weeks were generally similar in terms of mortality and mean time to death, regardless of inoculation route, except for the oral route, which had little effect. In comparison with the 1- and 2-week-old rats, the 4-week-old rats were less susceptible to the virus by all routes. Eight-week-old rats inoculated by the i.ci.n. or s.c. routes died, but all those inoculated by other routes survived. To follow the spread of virus in the central nervous system, 4-week-old rats inoculated by the i.c. route were examined. The virus was first detected in the brain on day 1 and in the spinal cord on day 2. The viral titres in both tissues reached a plateau of 10(7)plaque-forming units (PFU)/0·2 g by day 4, at which time clinical signs had developed. By immunohistochemical analysis, virus-specific antigen was found first in the pyramidal cells of the hippocampus and cerebral cortex, and later in the large-sized neurons of the pons and spinal cord. Still later (day 4) immunolabelling was found in Purkinje cells of the cerebellum, but not in the ependymal cells, choroid plexus or other glial cells.